Salient features of medical nanoparticles in biological fluids from an analytical ultracentrifuge. Issue 44 (6th November 2020) - Cinar, Gizem; Englert, Christoph; Schubert, Ulrich S.; Nischang, Ivo
Abstract : Deciphering the behavior of degradable nanoparticles in biological fluids is demonstrated by interference-free assessment. The resultant vastly different erosion characteristics provide a necessary stepping stone for their design toward translation. Abstract : From the perspective of future translation, medical, biodegradable nanoparticles (NPs) have been investigated using an analytical ultracentrifuge in fluids of various complexity, including human serum, in the temperature range of 6 to 40 °C, and timescales relevant for a nanomedical targeting and clearance application. These studies provided salient insights into the integrity and degradation aspects of the NPs, imposed by varying solution environmental conditions. This was enabled by selective monitoring of the targeting dye moiety, cell-specifically directing the NPs to the desired location of interest, i.e. considering a future translative in vivo application. Our study provides experimental insights that are believed to be of key importance to gauge the feasibility of such translative applications in terms of (i) compatibility with patient sera, (ii) timescales of targeting success, and (iii) timescales of desired erosion enabling clearance from the target. All such aspects are provided a priori any in vivo implementation.